Drug-related problems in the elderly - Midlöv, Patrik; Eriksson, Tommy; Kragh, Annika (Springer Netherlands : Imprint: Springer, 2009)
Drug-related problems in the elderly is intended to serve as a source of information and clinical support in geriatric pharmacotherapy for students as well as all health care professionals, e.g. physicians, nurses and pharmacists. Pharmacotherapy is of great importance to all mankind. Drugs are however powerful and must be handled appropriately. This is especially important for elderly patients. Drug-related problem is not a major subject in most university programmes in medicine or pharmacy. When there is no speci c course, there is often no book covering the topic. In our view, as teachers at various university courses, there has been a shortage of literature that re ects the most important aspects of drug-related problems in the elderly. Medical practitioners, nurses and pharmacists, need to have this knowledge to be able to serve their patients in the best way. This book covers most aspects of drug-related problems in the elderly. With b- ter knowledge of drug-related dif culties and risks we hope that elderly will have fewer drug-related problems and bene t more from their pharmacotherapy.